2020
DOI: 10.3390/ijms21031094
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation Mechanism of Alzheimer’s Amyloid β-Peptide Mediated by α-Strand/α-Sheet Structure

Abstract: Alzheimer’s disease (AD) is one of the most common neurodegenerative diseases and a widespread form of dementia. Aggregated forms of the amyloid β-peptide (Aβ) are identified as a toxic species responsible for neuronal damage in AD. Extensive research has been conducted to reveal the aggregation mechanism of Aβ. However, the structure of pathological aggregates and the mechanism of aggregation are not well understood. Recently, experimental studies have confirmed that the α-sheet structure in Aβ drives aggrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
(144 reference statements)
0
12
0
Order By: Relevance
“…Until its independent 'rediscovery' in the Daggett lab, the structure was dismissed and considered to be a rare and alternative conformation to the energetically favourable β-sheet, which is correct for normal, native proteins. Following its observation in MD simulations conducted by the Daggett lab, α-sheet structure has been observed in a number of other MD simulations of amyloid proteins [51][52][53][54][55][56].…”
Section: Toxic Oligomers Are Composed Of α-Sheet Structurementioning
confidence: 72%
See 3 more Smart Citations
“…Until its independent 'rediscovery' in the Daggett lab, the structure was dismissed and considered to be a rare and alternative conformation to the energetically favourable β-sheet, which is correct for normal, native proteins. Following its observation in MD simulations conducted by the Daggett lab, α-sheet structure has been observed in a number of other MD simulations of amyloid proteins [51][52][53][54][55][56].…”
Section: Toxic Oligomers Are Composed Of α-Sheet Structurementioning
confidence: 72%
“…Next, we sought to further validate the presence of α-sheet structure in our de novo peptides through MMS-IR, which reports on amide I band absorption (1714 cm −1 to 1590 cm −1 ) [ 52 ]. Amide I band absorption is correlated with shifts in hydrogen bonding patterns and dipole–dipole interactions, and can therefore aid in determining protein secondary structure [ 77 ].…”
Section: Determination Of Spectroscopic Signatures For α-Sheetmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, α-sheet formation is not unique to our simulation methods or force field. Other investigators have also observed α-sheet in silico using other simulation packages and other force fields, including TTR (AMBER program, parm94 force field), 68 α-synuclein (GROMACS, CHARMM27), 69,70 β-amyloid peptide (GROMACS, CHARMM36m), polyglutamine (GROMOS, GROMOS96), 71 and others. [72][73][74][75][76] By way of comparison, we point out that we do not observe α-sheet formation in "normal" proteins.…”
Section: α-Sheet May Play a Role In P53 Aggregationmentioning
confidence: 99%